Alk5/Runx1 signaling mediated by extracellular vesicles promotes vascular repair in acute respiratory distress syndrome. Issue 1 (22nd June 2018) - Shah, Trushil; Qin, Shanshan; Vashi, Mona; Predescu, Dan N.; Jeganathan, Niranjan; Bardita, Cristina; Ganesh, Balaji; diBartolo, Salvatore; Fogg, Louis F.; Balk, Robert A.; Predescu, Sanda A.
Abstract: Background: Pulmonary endothelial cells' (ECs) injury and apoptotic death are necessary and sufficient for the pathogenesis of the acute respiratory distress syndrome (ARDS), regardless of epithelial damage. Interaction of dysfunctional ECs with circulatory extracellular vesicles (EVs) holds therapeutic promise in ARDS. However, the presence in the blood of long‐term ARDS survivors of EVs with a distinct phenotype compared to the EVs of non‐surviving patients is not reported. With a multidisciplinary translational approach, we studied EVs from the blood of 33 patients with moderate‐to‐severe ARDS. Results: The EVs were isolated from the blood of ARDS and control subjects. Immunoblotting and magnetic beads immunoisolation complemented by standardized flow cytometry and nanoparticles tracking analyses identified in the ARDS patients a subset of EVs with mesenchymal stem cell (MSC) origin (CD73 + CD105 + Cd34 − CD45 − ). These EVs have 4.7‐fold greater counts compared to controls and comprise the transforming growth factor‐beta receptor I (TβRI)/Alk5 and the Runx1 transcription factor. Time course analyses showed that the expression pattern of two Runx1 isoforms is critical for ARDS outcome: the p52 isoform shows a continuous expression, while the p66 is short‐lived. A high ratio Runx1p66 / p52 provided a survival advantage, regardless of age, sex, disease severity or length of stay in the intensive care unit. Moreover, the Runx1p66 isoform is transiently expressed by cultured human bone marrow‐derived MSCs, it is released in the EVs recoverable from the conditioned media and stimulates the proliferation of lipopolysaccharide (LPS)‐treated ECs. The findings are consistent with a causal effect of Runx1p66 expression on EC proliferation. Furthermore, morphological and functional assays showed that the EVs bearing the Runx1p66 enhanced junctional integrity of LPS‐injured ECs and decreased lung histological severity in the LPS‐treated mice. Conclusions: The expression pattern of Runx1 isoforms might be a reliable circulatory biomarker of ARDS activity and a novel determinant of the molecular mechanism for lung vascular/tissue repair and recovery after severe injury.